Charm muska at the Gagauz in the context of religious identity and ethnocultural parallels - Elizaveta N. Kvilinkova (Историческая этнология, 2022)
In the article, traditional medicine is considered as part of traditional knowledge, which is one of the components of folk culture and is preserved by word-of-mouth. It is noted that each ethnic group has developed its own arsenal of folk methods of treatment, which is associated with folk traditions, religious beliefs and economic activities. The object of the author’s special study is the amulet «muska» (a small triangular object), which occupies a special place in the folk medicine of the Gagauz and is preserved at the present time. Based on the field material, the methods of its manufacture and wearing are analyzed, the manifestation of religious identity forms is studied. The data is given on similar amulets common among other peoples (Bulgarians, Turks, Tatars, etc.). It is concluded that the Gagauz have preserved archaic methods of making musky. In most cases, they use medicinal plants that perform the function of a talisman. Some items invested in the amulet reflect the confessional affiliation of the Gagauz – Orthodoxy. Considering the tradition of wearing amulets as part of the traditional culture of the people, as well as identifying the existing ethno-cultural parallels in this area, the author “fits” it into the historical and cultural context.